2013
DOI: 10.4028/www.scientific.net/amm.364.589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isothermal-Rolling Process on the Morphology, Size and Distribution of Type II MnS

Abstract: The effect of isothermal-rolling process on the morphology, size and distribution of type II MnS was studied based on Gleeble-1500 simulator. The experimental results show that the relative plasticity of type II MnS increases with deformation temperature decreasing, but, it increases first and then decreases with deformation amount increasing; Heavy compression deformation is beneficial to improve the distribution of type II MnS; The changing trends of the size of type II MnS for varying deformation amount are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…These minerals could originate from geological materials such as soil, road dust or gravel from around the rails. S-containing particles found in the subway PM 2.5 could be associated with friction between rails and brakes, because S is a component of railway steel in China Xia et al, 2008). Our results agree with those of Bao (2009), who reported that S could be found in Shanghai …”
Section: 2supporting
confidence: 93%
See 1 more Smart Citation
“…These minerals could originate from geological materials such as soil, road dust or gravel from around the rails. S-containing particles found in the subway PM 2.5 could be associated with friction between rails and brakes, because S is a component of railway steel in China Xia et al, 2008). Our results agree with those of Bao (2009), who reported that S could be found in Shanghai …”
Section: 2supporting
confidence: 93%
“…The Mn is also likely to be produced from processes at railwheel-brake interfaces, because Mn is another component of Chinese rail steel Xia et al, 2008). Ba and Ga levels were highly correlated with those of Fe in Shanghai subway PM 2.5 (R 2 = 0.97 and R 2 = 0.99 respectively).…”
Section: Chemical Elements In Pm 25mentioning
confidence: 91%
“…[12] In most cases, type II sulfides are in the majority in high-sulfur steels. They are more harmful to the steel property and steel quality than type I and type III sulfides, [13][14][15][16] because the real size of type II sulfides is usually much larger than type I and type III sulfides. In addition, type II sulfides will be easily deformed into long strips during the rolling process due to the large size, leading to the anisotropy of steel properties and causing cracks in the steel.…”
mentioning
confidence: 99%